Sulh (mediation) in the state of Selangor: an analysis of legal provision and its application - Ahmad, Sa'odah; Abdul Hak, Nora (IIUM Press, 2010)
The first part of the paper seeks to examine the relevant legal provisions of ṣulḥ in the State of Selangor Darul Ehsan. Thus, the provisions of ṣulḥ as provided for under the Islamic Family Law Enactment 2003 will be discussed and analysed. Other provisions under the Administration of Islamic Religious Enactment 2003, the Syariah Court Civil Procedure Enactment 2003 and the Civil procedure (ṣulḥ) Rules 2001 will also be examined to study the procedures and guidelines in conducting Majlis ṣulḥ. The qualification of ṣulḥ officer will be briefly discussed in the last part of the paper. The paper concludes by commending the initiative that has been taken by the Department of Syariah Judiciary of Selangor in introducing ṣulḥ which has been proven to be very effective in reducing excess cases in the State Syariah Courts.